Analisis Faktor Sikap Tanggap Bencana Banjir Bagi Anak Usia Dini - Sufi, Wasiah; Efastri, Sean Marta (PAUD Lectura: Jurnal Pendidikan Anak Usia Dini, 2025)
Teachers play a crucial role in fostering disaster preparedness understanding among children, particularly within the context of the newly implemented Merdeka Curriculum. In early childhood education, learning is generally play-based since the main concept is learning through play. This approach enhances children’s learning experiences, imagination, and critical thinking skills. Disaster preparedness education, especially regarding floods, is essential for all levels of society, including young children. Floods not only pose risks of drowning and drifting but also threaten health due to contaminated water; therefore, children need to understand that floodwater is harmful and can cause illness. Through engaging learning activities, children are expected to understand how to protect themselves during flood events. The study results show that for the knowledge and attitude indicators, children achieved an average score of 89.73%, indicating good comprehension. The emergency planning indicator reached an average of 88.06%, while the warning system indicator obtained the lowest average of 85.84%. Meanwhile, the resource mobilization indicator achieved the highest average score of 95.84%. Overall, children’s level of understanding regarding flood disaster response attitudes reached 90%, categorized as very good.